Ion separation from dilute electrolyte solutions by nanofiltration - Garcia, Corazon M. (2000)
Nanofiltration (NF) is a pressure-driven process which is considered potential for the separation of ionic species selectively from solutions containing mixture of electrolyte solutes. The lower operating pressure requirement of NF than reverse osmosis (RO) makes the earlier potentially economical. In the separation of ions, many authors believed that there are membranes with characteristic fixed surface charge and that the mechanism of separation of ions is by the differences in valences of the ions.